Efficient (Bio)emulsification/Degradation of Crude Oil Using Cellulose Nanocrystals - Petr Sitnikov; Philipp Legki; Mikhail Torlopov; Yulia Druz; Vasily Mikhaylov; Dmitriy Tarabukin; Irina Vaseneva; Maria Markarova; Nikita Ushakov; Elena Udoratina (Polysaccharides, 2023)
This study has investigated the influence of cellulose nanocrystals (CNCs) with partially acetylated surfaces on the formation, stability, rheology and biodegradability of the Pickering emulsion in a crude oil/water (co/w) system. In all investigated systems, it was observed that the CNC concentrations of 7 mg/mL led to the emulsions showing stability over time. It was also noticed that the increase in concentration of background electrolyte (NaCl) leds to the droplets of emulsions becoming smaller. It was demonstrated that the rheology of the o/w emulsions of the oil products and crude oil stabilized by CNCs depends, to a large extent, on the colloid chemical properties of nanocellulose particles. Calculations and experimental methods were used to study the changes in the acid–base properties of CNCs on the surface of emulsion droplets, depending on a type of hydrophobic components (crude oil and liquid paraffin). The formation of Pickering emulsions leads to the oxidation of oil by Rhodococcus egvi in aerobic conditions becoming more effective, provided that the environment includes mineral salts of nitrogen, potassium and phosphorus. The results obtained present a scientific basis for the development of technologies for the disposal of oil spills on water surfaces.